The Role of the MGMP in the Implementation of the Curriculum for the Subject of Islamic History at Islamic Senior High School Yogyakarta in 2019 - Tsuroyya, Elfa; Arif, Mahmud (Program Studi Pendidikan Agama Islam, 2021)
This study reveals the role of MGMP SKI MA DIY in implementing KMA 183 and 184 in 2019. This research is a descriptive-analytical qualitative research. This study was conducted in Yogyakarta at the MGMP SKI MA DIY. Interviews, documentation, and observations were used to collect data. The study finds out that these roles include socialization, implementation, and monitoring of policies. Not only internal management meetings, but also management meetings with MGMP members are also held to socialize policy implementation. The policy is implemented in two ways: the determination of the work program as a guide for field activities, and the implementation of the work program as an MGMP progress report. Monitoring policy implementation uses two methods: extracting information from FGDs and distributing Google forms to track policy implementation. This research helps to develop MGMP MA SKI DIY in the future curriculum development.